‘I Care, You Deserve’ Module in helping pedophilia victims - Norhidayah Daud; Faizah Abd Ghani (RedWhite Press, 2020)
‘I Care, You Deserve’ Module is a module for pedophilia victims. This module has been developed based on the research findings on the effects of pedophilia to the victims. This module includes four main aspects which are spiritual, cognitive, emotion and behaviour. Pre and post-module on the psychological well-being level has been done to test the effectiveness of the module application. The result shows that this module is helpful in providing improvement to the victims for their well-being.